PRODUCTIVE PERFORMANCE, SOME HEMATOLOGICAL TRAITS AND GENETIC RELATIONSHIP IN DIFFERENT LOCAL QUAIL AFFECTED BY DIETING THE RAPESEED (CANOLA) SEEDS POWDER - Hurea Abdulrazaq; sheren mahmud; Jenan najdat; Sardar Sardare (Mesopotamia Journal of Agriculture)
The impact of dietary supplementation with (2) levels of canola seed powdered and the effect of different local quails' lines and the influence of diet × line on the productive performance, Some hematological traits and genetic relationship, has to be investigated in this study. A total of 162 laying quail in three lines color white; black; and yellowish-brown were randomly distributed to (3) treatment groups with (3) replicates/ treatment/ line T0: control (standard diet); T1 and T2 were standard diets supplemented with 1% and 3% canola seeds powder (CSP) respectively. The results of Genetic relationship using RAPD-PCR marker, noted that genetic similarity values range between 0.5 to 1. The highest number of bands was 28 among all groups used. The highest percentage of Polymorphisms observed in the primer OPA-14. The highest range of the molecular weight was (200 - 1500 bp). The basal diet supplemented with 3% of (CSP) had higher final body weight. There was a significant (P≤0.05) difference between line groups, as the brown line exhibited higher values for final body weight. It can be noted that T2 (3% CSP) the white line had a higher Feed intake. 1% and 3% (CSP) provided best feed conversion ratio. T1 (1% CSP) had higher egg mass, egg weight and hen-day egg production. T2 recorded highest levels since hematocrit level influenced. Generally, can be concluded and recommended that using 1%, 3% (CSP) had helped improve body metabolism and satisfactorily impacts performance and health in different local quail lines.